2022
DOI: 10.20945/2359-3997000000472
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of observational studies on the effects of epigenetic factors on serum triglycerides

Abstract: Epigenetic modifications might be associated with serum triglycerides (TG) levels. This study aims to systematically review the studies on the relationship between the methylation of specific cytosinephosphate-guanine (CpG) sites and serum TG levels. This systematic review and meta-analysis study was conducted according to the PRISMA 2020 (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. A systematic literature search was conducted in Medline database (PubMed), Scopus, and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Our study identified that cg01881899 of ABCG1 is a CpG site influenced by 7 meQTL for MetS (Table 3 ), and it is also associated with TG [ 48 ], BMI [ 49 ] and HOMA-IR [ 50 ]. However, there has been limited research on the association between meQTLs and these phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified that cg01881899 of ABCG1 is a CpG site influenced by 7 meQTL for MetS (Table 3 ), and it is also associated with TG [ 48 ], BMI [ 49 ] and HOMA-IR [ 50 ]. However, there has been limited research on the association between meQTLs and these phenotypes.…”
Section: Discussionmentioning
confidence: 99%